PENERAPAN ASAS NEBIS IN IDEM DALAM PERKARA PERBUATAN MELAWAN HUKUM OLEH MAHKAMAH AGUNG ATAS UPAYA HUKUM LUAR BIASA “PENINJAUAN KEMBALI”: Kajian Putusan Mahkamah Agung Republik Indonesia Nomor 405 PK/PDT/2017 - Hariadi (Fakultas Hukum Universitas Gunung Rinjani, 2020)
This study aims to find out how the Supreme Court decidescases of unlawful acts with the principle of nebis in idem andthe basis for consideration of the Supreme Court justicesexamining and deciding Case Number 405 PK / Pdt / 2017,related to the principle of nebis in idem. This research is a typeof normative law, with a normative juridical approach, namelydoctrinal law research which refers to legal norms. emphasizessecondary sources of material, both regulations and legaltheories, and examines legal principles that are scientifictheoretical in nature and can be used to analyze the problemsdiscussed. The method of analysis of normative legal researchis in the form of a prescriptive method, namely a method ofanalysis that provides an assessment (justification) of theobject under study whether it is true or false, or what shouldbe according to law.